Assessing economic trends in Ireland and Northern Ireland - Alan Barrett, Adele Bergin (ESRI, 2025)
This report is the first in a planned annual series examining the structure and performance of the economies of Ireland and Northern Ireland. At one level, this report builds on previous work under the Shared Island initiative, in particular Bergin et al. (2025), and presents comparable data on the economies of Ireland and Northern Ireland. However, given that this is the first report in the new series, another objective is to explore how future reports might be structured whereby the series will provide an ongoing, evidence-based evaluation of key indicators across the two jurisdictions, highlighting areas of convergence and divergence, and identifying data gaps that limit north-south analysis. By establishing this foundation, the report seeks to develop further a joint understanding of the economies of Ireland and Northern Ireland, support policy development, inform future research, and encourage greater collaboration on shared challenges and opportunities across the island.